ВИВЧЕННЯ ЛІТЕРАТУРИ В КОНТЕКСТІ КУЛЬТУРИ - Назаренко, Надія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття містить обґрунтування компаративізму як наукової парадигми сучасного гуманітарного знання. Література розглядається як прояв духовної культури людства. На відміну від світової літератури, що констатує універсалізацію мистецького мислення і включає в своє річище чисельні національні літератури, літературознавча компаративістика зіставляє будь-які явища різноманітних літератур. Зазначено, що вивчення порівняльного літературознавства в європейських та українських університетах є одним з пріоритетів мовно-літературної підготовки фахівців з філології. Наведено приклади апробації науково-дослідницької роботи студентів ОР «Магістр» з компаративістики. Статья содержит обоснование компаративизма как научной парадигмы современного гуманитарного знания. Литература рассматривается как проявление духовной культуры человечества. В отличие от мировой литературы, которая констатирует универсализацию художественного мышления и включает в свое русло многочисленные национальные литературы, литературоведческая компаративистика сопоставляет любые явления различных литератур. Отмечено, что изучение сравнительного литературоведения в европейских и украинских университетах является одним из приоритетов языковой и литературной подготовки специалистов по филологии. Приведены примеры апробации научно-исследовательской работы студентов ОР «Магистр» в сфере компаративистики. The article contains a study of comparativism as a scientific paradigm of modern humanities. Literature is considered as a manifestation of the spiritual culture of mankind. In contrast to the world literature that states the universalization of artistic thinking and includes numerous national literatures into its course, comparative literature studies compare literary phenomena in any different literatures. It was noted that the study of comparative literature in the European and Ukrainian universities is a priority of language and literary training of specialists in philology. A fundamental project of comparative literature is to cultivate reading across linguistic boundaries in order to highlight everything that the exclusive focus on a national literature tends to obscure. Students of comparative literature trace the transformations and travels of literary genres and texts across time and space. They explore the connections of literature with history, philosophy, politics, and literary theory. And they study the intersections of literature with other cultural forms such as film, drama, the visual arts, music, and new media. In our increasingly globalized age, translation studies are also an important part of the comparative approach to literature.